2001
DOI: 10.1136/bmj.323.7309.363
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of adverse birth outcomes in populations living near landfill sites

Abstract: Objective To investigate the risk of adverse birth outcomes associated with residence near landfill sites in Great Britain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
4
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(225 citation statements)
references
References 28 publications
4
207
4
4
Order By: Relevance
“…18 In the United Kingdom, where around 80% of the population lives within 2 km of a solid waste landfi ll site, two large population-based studies found excess numbers of congenital defects that could not be explained by other possible causes, 5,6 even considering the infl uence of confounding variables and other methodological problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In the United Kingdom, where around 80% of the population lives within 2 km of a solid waste landfi ll site, two large population-based studies found excess numbers of congenital defects that could not be explained by other possible causes, 5,6 even considering the infl uence of confounding variables and other methodological problems.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined possible associations with adverse outcomes from pregnancy, such as occurrences of congenital abnormalities, 2,5,6,12,14 Considering the lack of studies evaluating the risks relating to such areas within the Brazilian context, the aim of the present study was to evaluate the association between living close to solid waste landfi ll sites and occurrences of cancer and congenital malformations among these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Two epidemiological studies reported a possible relationship between exposure to pesticides and hypospadias. Kristensen reported a moderate increase in the odds ratio (OR) for hypospadias in individuals exposed to farm chemicals (OR = 1.51, 95% confidence interval, 1.00-2.26) [66], and Weidner [67,68] A c c e p t e d M a n u s c r i p t sites has been associated with a high incidence of hypospadias [69,70]. Similarly, an increased rate of hypospadias was reported in boys from parents exposed to dioxin after the Seveso industrial accident [71].…”
Section: Ii-1 Arguments For An Environmental Contributionmentioning
confidence: 99%
“…In view of the limited locational accuracy of the data, a 2 km buffer zone was used: finer subdivision of distance from landfill sites (e.g. by constructing 1 km buffer zones) was not considered meaningful (Elliott et al, 2001a). The 2 km resolution used in this study was similar to or higher than that of previous studies (Dolk et al, 1998;Fielder et al, 2000) and at the likely limit of dispersion for landfill emissions to include both air and water pathways, and possible dispersion by birds or animals (WHO, 2000;Elliott et al, 2001a).…”
Section: Data Preparationmentioning
confidence: 99%